Oat starch extraction process: review study (Research, Society and Development, 2023)
Oats belong to the Aveneae genus of the Gramineae family, it is a temperate cereal and 60% of the dry matter of the grain is composed of starch. Each starch source is unique in nature and has different characteristics that determine its suitability for a specific application. Starch stands out for ensuring benefits in its technological applications and for ensuring the possibility of extraction from various plant sources. In this scenario, cereals stand out because they contain a high concentration of starch in their composition. The present work aims to carry out a bibliographical review on the process of extracting oat starch. A systematic review of the literature was carried out using the following databases: PubMed; Scielo; Mendley and Google Scholar, where 110 articles were found, and of these 55 were selected for writing the bibliographic review. It is concluded that there are few studies related to the extraction and use of oat starch for industrial purposes.